2020
DOI: 10.3390/molecules25081968
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Antioxidant Activity and Flavonoids Metabolites in Peel and Flesh of Red-Fleshed Apple Varieties

Abstract: In this research, we compared the phenotypical characters, total anthocyanins content, total phenols content, and antioxidant activity of red-fleshed apple cultivars 'XJ4', 'QN-5', 'DH' and 'HX1' at three fruit developmental stages. A further flavonoids metabolites study was conducted in 'XJ4' and 'DH'. We found broader variation of total anthocyanins content in the peel of the four cultivars, which might result in larger differences of free radicals scavenging rate. The most significant difference in fruit ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 35 publications
1
24
0
1
Order By: Relevance
“…This observation is in agreement with previous studies [27,37] and can be rationalized with enzyme activities that are modulated by the exposure of fruits to the sun [27]. Furthermore, a higher level of anthocyanins in the peel than in the pulp is found, and this difference in the concentrations of phytochemicals in these different parts of apples is in accordance with other studies [25,40,41].…”
Section: Apple Pulp: the Polyphenolic Profilesupporting
confidence: 93%
“…This observation is in agreement with previous studies [27,37] and can be rationalized with enzyme activities that are modulated by the exposure of fruits to the sun [27]. Furthermore, a higher level of anthocyanins in the peel than in the pulp is found, and this difference in the concentrations of phytochemicals in these different parts of apples is in accordance with other studies [25,40,41].…”
Section: Apple Pulp: the Polyphenolic Profilesupporting
confidence: 93%
“…The anthocyanins in the juice of blueberry showed strong antioxidant activity to superoxide anion free radicals [25]. In addition, in our previous studies, it was found that red-fleshed apples have significant antioxidant capacity in vitro [26,27]. However, studies on the reduction of furan content in the process of coffee, simulated furan solutions, and not-from-concentrated (NFC) juices by anthocyanins are very limited, and anthocyanin extracts are likely to be used as inhibitors for furan formation.…”
Section: Introductionmentioning
confidence: 93%
“…Anthocyanins belong to flavonoid compounds, a class of plant pigments that widely exist in nature (11). It is well-known that anthocyanins, as effective natural antioxidants, play vital roles in protecting human against diseases, such as cancer, diabetes, and hyperglycemia, and maintaining normal vascular permeability (12).…”
Section: Introductionmentioning
confidence: 99%
“…Red-fleshed apple [Malus sieversii f. neidzwetzkyana (Dieck) Langenf] is attractive to consumers because of visual skin, red flesh color, high anthocyanin content, and other bioactive phytochemicals (19,20). Anthocyanin extracts from red-fleshed apple had a strong ability to scavenge DPPH, superoxide anions, and hydroxyl radicals, which further reduced the level of oxidative stress and exhibited stronger antioxidant capacity (11,21,22). The previous study on the treatment of porcine granulosa cells with anthocyanins extracted from the mesocarp of red-fleshed apple indicated an alleviating effect on oxidative damage (23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation